Gelling, textural, and sensory properties of grass jelly formulated with different starches - Shiyun Zhou; Maninder Meenu; Baojun Xu (Food Production, Processing and Nutrition)
Abstract Starch from different sources exhibits different properties when used as an ingredient for developing a food. There are many recipes reported to produce grass jellies from different starches. However, the impact of starch from a particular source on the quality of grass jelly has not been explored untill now. Thus, in present study, blume polysaccharide extract from mesona herb was mixed with starch slurries from 14 different sources while boiling to prepare grass jellies. These grass jellies were further investigated for their microstructure, color, cohesiveness, gumminess, hardness, springiness, and chewiness to explore the impact of starch source of grass jellies quality. Among all the starches, the pea starch-based grass jelly presented the highest texture qualities in terms of hardness, gumminess, and chewiness. Whereas corn starch-based grass jelly exhibited higher values for cohesiveness and springiness. Overall, grass jelly formulated with pea and corn starch performed well in terms of texture properties analysis among other samples. The canna grass jelly was the most preferred by panelists in terms of sensory properties. All samples showed to have a network structure under scanning electron microscopy (SEM). The color of all jelly samples was dark and an insignificant difference was observed in color values of all the samples. Based on all parameters discussed in this study, pea starch, corn starch and canna starch are highly preferred for producing grass jelly from Chinese dry mesona herb. As the grass jellies formulated with pea starch, corn starch, and canna starch exhibit improved quality parameters, more studies need to be conducted to further explore the optimal proportion of these starches and herbal extracts as well as their impact on gelation for developing novel grass jellies. In addition, the viscoelastic properties of formulated grass jelly samples also need to be explored to understand addition properties. It is also important to explore the reason behind the high values for the textual properties of pea starch grass jelly compared to 13 other grass jelly samples formulated with different starch sources. Graphical Abstract